The main characteristics of the leader channel during breakdown of a long air gap by high pulse voltage - M. I. Baranov (Electrical engineering & Electromechanics)
Goal. Calculation-experimental determination of basic descriptions of plasma channel of leader at an electrical breakdown of long air gap in the double-electrode discharge system (DEDS) «edge-plane» by artificial electricity of high pulse voltage of positive polarity. Methodology. Bases of the theoretical electrical engineering and electrophysics, electrophysics bases of technique of high and extra-high voltage, large pulse currents and high electromagnetic fields, basis of high-voltage pulse and measuring technique. Results. The simplified electrophysics model of origin and development of positive leader is offered in the long air gap of probed DEDS, which the followings descriptions of plasma channel of this positive leader were found on the basis of: a closeness of neL charge and electric potential UeL in the head of leader; linear charge qLl of leader of plasma channel; closeness δeL of electron current ieL and this current ieL in the channel of leader; strength of high electric field outside ELe and inwardly ELi of the channel of leader; length ls of streamer area before the head of leader; maximal electron temperature TmL in plasma of channel of leader; linear active resistance RLl and active resistance RLc of channel of leader. Executed on a domestic powerful over-high voltage electrical equipment outdoors in the conditions of electrophysics laboratory high-voltage experiments with the use of standard interconnect aperiodic pulse of voltage Ue(t) of temporal shape of Tm/Tp≈200 μs/1990 μs of positive polarity for probed DEDS at a change in it of minimum length lmin of its discharge in air gap in the range of 1 m≤lmin≤4 m confirmed power and authenticity of row of the got calculation correlations for the indicated descriptions of plasma channel of positive leader which is formed and develops in this DEDS. Originality. In a complex kind calculation-experimental way the indicated basic descriptions of plasma channel of positive leader are certain in probed DEDS. By calculation way it is first rotined that on the stage of development of positive leader in atmospheric air of indicated DEDS high electric potential UeL of his spherical head with the charge of qeL≈58,7 nC has a less value (for example, UeL≈605 kV for length of his channel of lL=0,395 m at lmin=1,5 m) the radius of ReL≈0,5 mm, what high potential Ue(t)≈Ue(Td)≈611,6 kV its active metallic electrode-edge. Obtained result for the maximal electron temperature TmL≈1,639·104 K in plasma of the probed leader testifies that this plasma is thermo-ionized. Practical value. Practical application in area of industrial electrical power engineering, high-voltage pulse technique, techniques of high and extra-high voltage of the obtained new results in area of physics of gas discharge allows not only to deepen our electrophysics knowledges about a leader discharge in atmospheric air but also more grounded to choose the air insulation of power high and over-high voltage electrical power engineering and electrical engineering equipment, and also to develop different new electrical power engineering and electrophysics devices in area of industrial electrical power engineering and powerful pulse energy with enhanceable reliability and safety of their operation in the normal and emergency modes. References 49, figures 7.